The recombinogenic history of turnip mosaic potyvirus reveals its introduction to Japan in the 19th century. Issue 2 (24th June 2022) - Kawakubo, Shusuke; Tomitaka, Yasuhiro; Tomimura, Kenta; Koga, Ryoko; Matsuoka, Hiroki; Uematsu, Seiji; Yamashita, Kazuo; Ho, Simon Y W; Ohshima, Kazusato
Abstract: Characterizing the detailed spatial and temporal dynamics of plant pathogens can provide valuable information for crop protection strategies. However, the epidemiological characteristics and evolutionary trajectories of pathogens can differ markedly from one country to another. The most widespread and important virus of brassica vegetables, turnip mosaic virus (TuMV), causes serious plant diseases in Japan. We collected 317 isolates of TuMV from Raphanus and Brassica plants throughout Japan over nearly five decades. Genomic sequences from these isolates were combined with published sequences. We identified a total of eighty-eight independent recombination events in Japanese TuMV genomes and found eighty-two recombination-type patterns in Japan. We assessed the evolution of TuMV through space and time using whole and partial genome sequences of both nonrecombinants and recombinants. Our results suggest that TuMV was introduced into Japan after the country emerged from its isolationist policy (1639–1854) in the Edo period and then dispersed to other parts of Japan in the 20th century. The results of our analyses reveal the complex structure of the TuMV population in Japan and emphasize the importance of identifying recombination events in the genome. Our study also provides an example of surveying the epidemiology of a virus that is highly recombinogenic.